2020
DOI: 10.3920/bm2019.0098
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Bifidobacterium longum 51A attenuates intestinal damage and inflammatory response in experimental colitis

Abstract: This study evaluated the effects of Bifidobacterium longum 51A on the intestinal mucosa and inflammatory response in experimental colitis. Colitis was induced by administration of 3.5% dextran sodium sulphate (DSS) solution for 7 days. Two periods of administration were performed: treatment (T) group, mice received Bifidobacterium only during disease induction (7 days); total treatment (TT) group, mice received Bifidobacterium for 10 days before and during disease induction. The probiotic effects on intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…The results from this current study, therefore, provided evidence to demonstrate that indigo naturalis exert their protective effects on DSS-induced colitis by altering the structure and functionality of the gut microbiota. Notely, indigo naturalis treatment selectively promote the growth of protective strains, consistent with studies showing that increasing the abundance of these bacteria by drug or dietary interventions could relieve colitis (Devriese et al, 2017;Xie et al, 2019;Abrantes et al, 2020). Interestingly, most of them belong to producers of SCFAs, which are an important fuel for intestinal epithelial cells, and are known to strengthen the gut barrier function (Treem et al, 1994;Parada Venegas et al, 2019), and promote innate and adaptive immune cell generation (Russo et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…The results from this current study, therefore, provided evidence to demonstrate that indigo naturalis exert their protective effects on DSS-induced colitis by altering the structure and functionality of the gut microbiota. Notely, indigo naturalis treatment selectively promote the growth of protective strains, consistent with studies showing that increasing the abundance of these bacteria by drug or dietary interventions could relieve colitis (Devriese et al, 2017;Xie et al, 2019;Abrantes et al, 2020). Interestingly, most of them belong to producers of SCFAs, which are an important fuel for intestinal epithelial cells, and are known to strengthen the gut barrier function (Treem et al, 1994;Parada Venegas et al, 2019), and promote innate and adaptive immune cell generation (Russo et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
“…Besides that, it is recognized that the presence of the mucus in the gut prevents the adhesion of microorganisms to the mucosa and their translocation into the lumen (Grondin et al, 2020). Moreover, the mucus is important for the lubrication and protection of the intestinal epithelium from toxic substances coming from the external environment, such as DSS (Abrantes et al, 2020). Thus, in mouse colon inflammation caused by DSS intake, it is common to observe a decrease in goblet cell number, but it can be restored by the consumption of probiotic bacteria (Rodrigues et al, 2018;Zhang et al, 2018;Abrantes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mucus is important for the lubrication and protection of the intestinal epithelium from toxic substances coming from the external environment, such as DSS (Abrantes et al, 2020). Thus, in mouse colon inflammation caused by DSS intake, it is common to observe a decrease in goblet cell number, but it can be restored by the consumption of probiotic bacteria (Rodrigues et al, 2018;Zhang et al, 2018;Abrantes et al, 2020). It is important to highlight that MUC-2 is the major glycoprotein constituent of intestinal mucus and is secreted primarily by goblet cells (Perez-Vilar, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in cell and animal experiments have shown that Bifidobacterium longum strains regulate oxidative stress by enhancing the body's antioxidant activity and regulating the production and accumulation of ROS, thereby reducing the symptoms of IBD. B. longum 5(1A) administration in the dextran sulfate sodium-(DSS-) induced colitis in mice abated severe lesions in the colon with the decreased level of eosinophil peroxidase [40] (Figure 1). In addition, oral Bifidobacterium longum is also an effective treatment of ethanol-induced gastritis injury.…”
Section: Mechanisms Of Bifidobacterium Longum Inmentioning
confidence: 99%